The Validity of Eigendom Land Transitioning to Certificate of Building Rights Without Administration from the Village Head: Keabsahan Tanah Eigendom yang Beralih Menjadi Sertifikat Hak Guna Bangunan Tanpa Administrasi Dari Kepala Desa - Savier, Alem; Nafi’ah, Siti Basirotun; Aprillia, Tiara Rizky (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Land conversion is a crucial legal process in Indonesia's agrarian reform. Specific Background: The enactment of the 1960 Agrarian Law (UUPA) mandated the conversion of colonial land rights, including Eigendom, into the national land tenure system such as Sertifikat Hak Guna Bangunan (SHGB). Knowledge Gap: However, limited studies examine the legal implications when such conversions occur without formal administrative support from local authorities. Aims: This study investigates the legality of Eigendom land conversion into SHGB in the absence of administrative validation from the village head. Results: Using a normative juridical method and statutory interpretation, the study finds that the absence of administrative verification, particularly from the village head as the provider of land status information, undermines the legal validity of the SHGB conversion despite the presence of ownership evidence. Novelty: This research uniquely highlights the critical but often overlooked procedural role of local administrative involvement in legitimizing land rights transformation. Implications: The findings underscore the necessity of integrating formal administrative procedures to ensure legal certainty, minimize disputes, and strengthen public trust in land registration practices within Indonesia’s agrarian legal framework. Highlights: Highlights the legal impact of missing village administration in land conversion. Emphasizes the role of UUPA in transitioning colonial land rights. Stresses the need for administrative procedures to ensure validity. Keywords: Administration, Eigendom, Transition, Validity.